Effect of Organic and Inorganic Acid Pretreatment on Structural Properties of Rice Husk and Adsorption Mechanism of Phenol - Mukhtar, Hilmi (2011)
Rice husk treated with organic and inorganic acid was tested as a low cost adsorbent for the removal of phenol from artificial wastewater in batch adsorption procedure. The physical and surface properties of the developed adsorbents were characterized using FTIR and SEM. The efficiency of these adsorbents was evaluated by varying the adsorbent doses. A comparison of organic acid (citric acid) and inorganic acids HCL, H2SO4 and HNO3)treatment show that rice husk treated with organic acid (a weak acid) has less